Treatment with sera from water polo athletes activates AMPKa and ACC proteins In HepG2 hepatoma cell line - Polito, R.; Monaco, M. L.; Mallardo, M.; Elce, A.; Daniele, A.; Nigro, E. (Sport Sciences for Health, 2021)
Purpose: Physical activity and professional physical activity such as water polo (WP) sport, has numerous beneficial effects to fight metabolism-related disorders through several mechanisms, including the promotion of liver metabolic adaptations, and the modulation of cytokine production. The aim of this study was to investigate the effects of different types of physical activity on AMPKa and ACC, two proteins involved in liver metabolism; therefore, we treated the hepatoma cell line Hep G2 with sera from elite WP athletes and amateur (basket) players. As control, we used serum from both sedentary and obese subjects. Methods: Help G2 cells were treated with 5% of human sera from the different subjects; after 24 h and 48 h, HepG2 cell viability was verified through MTT assay and activation status of AMPKa and ACC through western blotting. Cytokine`s serum levels were measured through ELISA assay. Results: After 72 h, the treatment of HepG2 cells with sera from the different subjects produced no effect on cell viability. Furthermore, after 48 h of treatment, both AMPKa and ACC phosphorylation statistically increases in HepG2 cells treated with sera from WP athletes. Furthermore, IL-4, IL-6 and IL-10 levels resulted statistically increased in WP athlete`s sera than in sedentary subjects. Conclusion: The specific activation of AMPKa and ACC by WP sera confirms that professional sport activity carried out by WP athletes can be considered as a physiological activator of these two proteins also in HepG2 liver cells. In addition, the increase of anti-inflammatory cytokines in WP sera confirms the ample evidence for multiple anti-inflammatory activities carried out by WP discipline.